Iconic Events: Media, Politics, and Power in Retelling History - Leavy, Patricia (Lexington Books, 2007)
Iconic Events: Media, Power, and Politics in Retelling History examines the processes of collective memory surrounding traumatic events that have been deemed iconic in American culture. Leavy investigates the social and market forces that have shaped the meanings around and enduring significance of events that have captured the public's imagination, including Titanic, Pearl Harbor, Columbine, and September 11th. Iconic Events focuses on three interpretive phases that serve to mold public perception of these events: journalistic representations, political appropriations, and popular adaptations. With a vital, engaging approach, Leavy explores the processes by which traumatic events are made mythic in the public eye. Iconic Events is essential for collective memory scholars and undergraduate courses in communications, American studies, history, and sociology, as well as the general reader.